El Ilustrísimo señor don Juan José de Escalona y Calatayud. El obispo visitador- reformador del Obispado de Michoacán (1730-1735) - Martínez Cardoso, Lizeth (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
In the Catholic Church, bishops were considered the successors of the apostles of Christ, with sufficient power to govern their dioceses and take care of their sheep, because they were the shepherds in charge of bringing them spiritual food and taking care that they do not deviate from the path marked by the universal Church. To achieve this, the New Hispanic prelates were obligated to undertake the pastoral visit of their dioceses, which was one of the most arduous activities they had to carry out, ordered by the Council of Trent (1545-1563), the Mexican Provincial Council III (1585) and the Spanish monarch because of the patronage he enjoyed in Spanish America. The bishop of the diocese of Michoacán Juan José de Escalona y Calatayud (1729- 1737), who came to govern the bishopric after a long vacancy of eight years, first visited the episcopal city of Valladolid and, later, made the Visit of the Province of Chichimecas which was the most important region for the Michoacan Church. The visit, which he carried out with the support of his delegates, was undertaken with the purpose of personally know the area, imparting the sacrament of confirmation, but also with the objective of carrying out the pertinent reforms in the spiritual, administrative-parochial, disciplinary and moral issues, both among the clergy and the faithful, although those adjustments meant friction with the most powerful corporations of his jurisdiction.

En la Iglesia católica los obispos eran considerados los sucesores de los apóstoles de Cristo, con la potestad suficiente para gobernar sus diócesis y estar al cuidado de sus ovejas, ya que ellos eran los pastores encargados de llevarles el alimento espiritual y cuidar que no se desviaran del sendero marcado por la Iglesia universal. Para lograr lo anterior, los prelados novohispanos estaban obligados a emprender la visita pastoral de sus diócesis, la cual era una de las actividades más arduas que debían realizar, ordenada por el Concilio de Trento (1545- 1563), el Concilio III Provincial Mexicano (1585) y el monarca español en razón del patronato que gozó en la América española. El obispo de la diócesis de Michoacán Juan José de Escalona y Calatayud (1729- 1737), quien llegó a gobernar el obispado después de una larga vacante de ocho años, primero emprendió la visita de la ciudad episcopal de Valladolid y, posteriormente, realizó la visita de la Provincia de Chichimecas la cual era la región más importante para la Iglesia michoacana. La visita, que realizó con apoyo de sus delegados, la emprendió con el propósito de conocer personalmente la zona, impartir el sacramento de la confirmación, pero también con el objetivo de realizar las reformas pertinentes en lo espiritual, en lo administrativo parroquial, en lo disciplinar y en lo moral, tanto entre el clero como entre los fieles, aunque esos ajustes significaran roces con las corporaciones más poderosos de su jurisdicción.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2021-0850; Historia de México; Provincia de Chichimecas; Potestad; Reformas; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6493